2021
DOI: 10.3390/jcm10245752
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Computational Fluid Dynamics for Predicting Hemolysis in Mitral Paravalvular Leaks

Abstract: Paravalvular leaks (PVLs) may lead to hemolysis. In vitro shear stress forces above 300 Pa cause erythrocyte destruction. PVL channel dimensions may determine magnitude of shear stress forces that affect erythrocytes; however, this has not been tested. It remains unclear how different properties of PVL channels contribute to presence of hemolysis. A model of a left ventricle was created based on data from computer tomography with Slicer software PVLs of various shapes and sizes were introduced. Blood flow was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The information obtained thanks to imaging methods allowed for the visualization of stenoses and the creation of accurate CFD simulation models. CFD simulations can be a valuable tool in a wide range of blood flows in the circulatory system [10,27,[63][64][65][66][67][68][69][70][71][72][73], providing valuable information for physicians. CFD can provide information on high shear stress [10,[63][64][65], which is one of the factors causing blood hemolysis, which negatively affects patients' health [74].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information obtained thanks to imaging methods allowed for the visualization of stenoses and the creation of accurate CFD simulation models. CFD simulations can be a valuable tool in a wide range of blood flows in the circulatory system [10,27,[63][64][65][66][67][68][69][70][71][72][73], providing valuable information for physicians. CFD can provide information on high shear stress [10,[63][64][65], which is one of the factors causing blood hemolysis, which negatively affects patients' health [74].…”
Section: Discussionmentioning
confidence: 99%
“…CFD simulations can be a valuable tool in a wide range of blood flows in the circulatory system [10,27,[63][64][65][66][67][68][69][70][71][72][73], providing valuable information for physicians. CFD can provide information on high shear stress [10,[63][64][65], which is one of the factors causing blood hemolysis, which negatively affects patients' health [74]. In addition, computational methods allow for the improvement of stents [75][76][77][78][79][80][81][82] used in PCI, or allow one to obtain "virtual" results of FFR measurements [83][84][85][86][87][88].…”
Section: Discussionmentioning
confidence: 99%
“…LDH is a marker of hemolysis and has to be assessed after every percutaneous PVL closure, because in some cases hemolysis develops de novo or worsens after the procedure [ 3 ]. Based on computational fluid dynamics simulations we recently reported that some degree of hemolysis is always present in the case of PVLs even when this pathology does not manifest clinically [ 23 ]. Therefore it is expected that successful closure should decrease LDH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are underway to better understand how various properties of PVL channels can influence the likelihood of hemolysis. 11 The success of those complex structural procedures may depend on efficient multimodality imaging, which includes not only echocardiography and CCT but also novel imaging technologies such as 3D printing. 12–14…”
Section: Introductionmentioning
confidence: 99%